Design & performance of deep foundations in Ireland - Galbraith, Andrew P. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2011)
During the course of this study, a database of static load tests carried out on piles installed in varying ground conditions in Ireland, including fine and coarse grained soil and rock, was compiled. Site investigation data, including borehole logs and in-situ and laboratory test results pertaining to the soil at the various test sites, formed an essential part of the database.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin